Variação espacial e temporal de moscas-das-frutas (diptera: drosophilidae: Zaprionus) em pomares de goiaba no semiárido - Ribeiro, Lylian Souto (2024)
Brazilian fruit growing has reached the mark of 3rd largest producer in the world, however, the country occupies 23rd place among world fruit exporters. Fruit production occurs in all regions of the country, but predominates in areas with a tropical and subtropical climate, where the presence of fruit flies represents one of the main obstacles to the expansion of fruit growing activities. Given the rapid dispersion of drosophilids in Brazilian territory, the broad economic growth associated with fruit growing in the semi-arid region, the generalist habit and infestation capacity of Zaprionus, as well as the scarcity of information on the ecology and influence of habitats on the populations of these flies, This research aimed to evaluate associations between vegetation cover, temporal variation and climatic variables in the occurrence of fruit flies (Zaprionus spp.) in guava orchards in a sub-region of the Brazilian semi-arid region. The fruits were obtained through monthly collection during one year in two orchards, under different conditions of surrounding vegetation cover in Cariri Paraibano. A study of the abundance of drosophilids was also carried out using trays containing guava fruits. The results show that the environment around guava orchards influences the abundance and infestation of fruit flies of the genus Zaprionus, mainly due to air humidity and temperature in the Brazilian semi-arid region. The observations highlight the need for control at Fazenda Almas to prevent future damage. Furthermore, it is crucial to continue studies on these insect pests and their dispersal.